THE EXISTENCE OF THE PISOK DANCE AS A NEW CREATION DANCE IN THE MINAHASA ETHNIC - Sunarmi, Sri; Sundari, Riris Setyo (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2024)
The purpose of this research is to identify, classify and analyze the form and or construct choreographically of the Pisok dance. Qualitative research was conducted with several approaches, namely Ethno Art, role and presence, which used to describe the form of choreography by understanding the phenomena that become the awareness of the Minahasa people, also its relation to the role of the existence of Pisok as a New Creation Dance in the midst of the Minahasa people. The technique of data analysis used Ahimsa Putra theory. Choreographically, the Pisok dance was presented in single or group dance performances using the basic movements of bird dances in Minahasa, North Sulawesi, consist of basic traditional dance movements, from depicting the movements of birds flying, birds having fun with others by using the motion of the wings to flap in an agile way. It played by several female dancers in groups, usually is in an odd number. The motion vocabulary used was very simple, it describes; the basic pattern of the Pisok dance, the floor pattern or formation of the Pisok dance, the music used in the Pisok dance, and the make-up of the clothes worn on the Pisok dance. This Pisok dance is a reflection of the diversity and wealth of animals in Indonesia, which need to be preserved and developed both in terms of quality and in terms of dissemination to a wider audience.